THE ROLE OF AI TRANSLATION TOOLS IN SECOND LANGUAGE LEARNING - Matyakubova Laylo (Western European Studies, 2025)
This article explores the role of AI-powered translation tools in second language learning, focusing on their educational benefits, limitations, and implications for higher education. The rapid advancement of neural machine translation technologies, including widely used tools such as Google Translate and DeepL, has transformed the ways in which language learners access, interpret, and produce texts in a foreign language. These tools are increasingly employed to support reading comprehension, enhance vocabulary development, and assist with academic writing. Drawing on research in applied linguistics, second language acquisition, and educational technology, the article examines how AI translation tools can promote learner autonomy by facilitating independent learning and reducing linguistic barriers. However, it also critically addresses concerns regarding excessive reliance on machine translation, which may weaken learners’ active engagement with the target language and limit the development of grammatical awareness and communicative competence. In addition, the article considers ethical and pedagogical challenges related to AI-assisted learning, including issues of academic integrity and responsible use. It argues that AI translation tools should be integrated thoughtfully into language instruction as supportive resources rather than substitutes for traditional learning processes.
Keywords: AI translation tools; machine translation; second language learning